Restitution judges: A starting point for an agrarian jurisdiction as a guarantee of non-repetition in Colombia (2017)
The Colombian government and the main guerrilla, the farc, signed a peace agreement in November 2016. The establishment of an agrarian jurisdiction is one of the settlements they have reached. This article evaluates the already existing capacities the Colombian state has developed, based on an analysis of the ongoing land restitution process. Based on an analysis of some judicial decisions taken in the context of this process, and on three in-depth interviews with judicial operators involved in it, the article makes two main findings: the procedural innovations of the land restitution process and the application of the constitutional precept of the effective enjoyment of rights guarantee the effective access to justice for rural populations and to the social rights aimed at protecting and stabilising their property rights. For these reasons, these features will prove to be useful in the establishment of an agrarian jurisdiction in Colombia that will represent a guarantee of non-repetition. © 2017 by Koninklijke Brill NV, Leiden, The Netherlands.